The relative age effect in young athletes: A countywide analysis of 9-14-year-old participants in all competitive sports - Gil, S. M.; Bidaurrazaga-Letona, I.; Larruskain, J.; Esain, I.; Irazusta, J. (PLOS ONE, 2021)
The relative age effect (RAE) has primarily been investigated in male athletes involved in popular sports and high-level competitions. However, occurrence of RAE in other types of sports at the grassroots level, particularly in female athletes, is less well-studied. Thus, we examined the RAE in a large cohort of young athletes who participated in all competitive sports in Bizkaia, Spain, according to gender and specificity of the sport. The birth dates of 38,381 participants (65.1% males and 34.9% females) aged 9-14 years old in 37 competitive sports were analyzed. Birth dates were divided into four birth-quarters and compared to those of all children born in the same period using a Chi² goodness-of-fit test and standardized residuals. The effect size Cramer`s V was measured, and odds ratio and 95% confidence intervals were calculated to determine the odds of athletes born in January playing in the highest leagues. In the total sample, in boys RAE was evident in football, but only in higher-competition leagues (p<0.001, large effect size). In girls, RAE was evident in the most popular team sports: basketball (p<0.001, large effect size in basketball 1st league), handball and football (p<0.05, both small effect sizes). Players born in January were 3.23- and 2.89-times more likely to play in the 1st leagues than those born in December, for boys (football) and girls (basketball) respectively. In the overall analysis and in the remaining sports, presence of RAE was negligible. Therefore, the date of birth does not seem to be a constraint to participating in most sports in Bizkaia. The potential mechanisms for RAE are multifactorial and complex, yet a combination of factors, such as the popularity of a sport and the depth of competition, physicality and social influences may be involved. We discuss these mechanisms and potential measures to mitigate RAE.